PRICKLE2 revisited—further evidence implicating PRICKLE2 in neurodevelopmental disorders - Bayat, Allan; Iqbal, Sumaiya; Borredy, Kim; Amiel, Jeanne; Zweier, Christiane; Barcia, Guilia; Kraus, Cornelia; Weyhreter, Heike; Bassuk, Alexander G.; Chopra, Maya; Rubboli, Guido; Møller, Rikke S. (European journal of human genetics : EJHG, 2021)
PRICKLE2 encodes a member of a highly conserved family of proteins that are involved in the non-canonical Wnt and planar cell polarity signaling pathway. Prickle2 localizes to the post-synaptic density, and interacts with post-synaptic density protein 95 and the NMDA receptor. Loss-of-function variants in prickle2 orthologs cause seizures in flies and mice but evidence for the role of PRICKLE2 in human disease is conflicting. Our goal is to provide further evidence for the role of this gene in humans and define the phenotypic spectrum of PRICKLE2-related disorders. We report a cohort of six subjects from four unrelated families with heterozygous rare PRICKLE2 variants (NM_198859.4). Subjects were identified through an international collaboration. Detailed phenotypic and genetic assessment of the subjects were carried out and in addition, we assessed the variant pathogenicity using bioinformatic approaches. We identified two missense variants (c.122 C > T; p.(Pro41Leu), c.680 C > G; p.(Thr227Arg)), one nonsense variant (c.214 C > T; p.(Arg72*) and one frameshift variant (c.1286_1287delGT; p.(Ser429Thrfs*56)). While the p.(Ser429Thrfs*56) variant segregated with disease in a family with three affected females, the three remaining variants occurred de novo. Subjects shared a mild phenotype characterized by global developmental delay, behavioral difficulties ± epilepsy, autistic features, and attention deficit hyperactive disorder. Computational analysis of the missense variants suggest that the altered amino acid residues are likely to be located in protein regions important for function. This paper demonstrates that PRICKLE2 is involved in human neuronal development and that pathogenic variants in PRICKLE2 cause neurodevelopmental delay, behavioral difficulties and epilepsy in humans.